Implementation of Simple Smoke Houses to Increase Community Income in Selayar Village Southeast Maluku Regency - Anggeline L. Amahorseja; Dani S. Royani; Indah Rosulva; Kristhina P. Rahael; Sahrul Pora (Journal of Mandalika Social Science, 2025)
The partners in this community service program are a group engaged in processing and marketing grilled/smoked fish in Selayar Village, Southeast Maluku Regency, Maluku Province. The partners are categorized as economically productive community members. The problems faced by the partners include limited technology for anchovy smoking equipment, inadequate sanitation and hygiene in the production process, and a lack of knowledge in financial bookkeeping. Based on these issues, the proposed solutions include the application of a horizontal smoking device made from used drums, metal sheets, and iron materials, which is effective in maintaining the quality of smoked fish, as well as training in preparing simple business financial records. The main objective of this activity is to empower the group and increase their income in the production and marketing of smoked anchovies. The expected outputs of this program are the production of high-quality smoked anchovies and increased income for the partners. Referring to the identified problems, the methods used include discussions and mentoring, demonstrations and training, as well as continuous assistance to ensure effective technology transfer. This community service activity was conducted at the Selayar Village Office. Discussions, mentoring, and demonstrations were provided to improve the partners’ knowledge and understanding, training was conducted to enhance their skills, and assistance was provided to strengthen and sustain their capabilities.